Comparative study of catalysts for the oxidative coupling of methane - Burch, R; Squire, G; Tsang, S (1988)
Mg, Sm, Mn and La oxide and alkali-promoted oxide catalysts have been prepared and tested for the oxidative coupling of methane. The results show for the alkali-promoted oxides that at steady state the selectivity for the formation of C2 products increases in the order La